Efforts of Islamic Religious Education Teachers in Addressing Eighth Grade E Students Who are Unable to Read The Qur'an at Smp Negeri 40 Medan - Nasro, Wanna Shyrati; Harahap, Abdi Syahrial (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2025)
The objectives of this research are 1) To determine the efforts of PAI teachers in overcoming difficulties in reading the Al-Qur'an in class VIII E of SMP Negeri 40 Medan, 2) To determine the supporting and inhibiting factors for PAI teachers in reading the Al-Qur'an in class VIII E of SMP Negeri 40 Medan. This research is a type of field research (field research) and is descriptive qualitative in nature. Data sources in this research include primary sources and secondary sources. Data collection was carried out by interviews, observation and documentation. The research results show that the PAI teacher's efforts are optimal for the students, because the teacher is required to solve the problems that exist within the students. One effort to overcome students' difficulties in reading the Al-Qur'an is by applying the talaqqi method where students imitate the PAI teacher's reading of the Al-Qur'an